The basic elements in planning Arab Islamic cities - Sahab, Ayed wasamiy (Al-Adab Journal, 2015)
The Arabic-Islamic city planning was based on two main factors are a place of worship, housing, and there is always the trinity of religious, political, and economic are at the center of each city, such as mosque ,Dar Emirate and the market in addition to the spacious field. But many Arab countries have adopted Western ideas in architecture and planning, which led to blur features and elements of originality in the planning of Arabic-Islamic city.many of the planners and engineers were adapted the Western ideas in architecture and planning until it became mainstream, And if it continues may lead to a change in values ​​and the Arab community lose their recognized civilization and indelible personal characteristic. I have addressed in this paper the originated of Arabic Islamic cities and study the basic elements in the planning and urban fabric of the component properties with a view to reaching elements of originality, which was characterized by the Islamic -Arab cities that can be used in the planning of contemporary Arabic city